ANALISIS PENINGKATAN KUALITAS PELAYANAN BONGKAR MUAT BARANG DI PELABUHAN PROBOLINGGO (Studi Kasus PT Delta Arta Bahari Nusantara Cabang Probolinggo) - Ardhian Trilaksono; Indung Sudarso (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
PT Delta Arta Bahari Nusantara is a regional-owned company owned by the East Java region as a loading and unloading operator for the Probolinggo port trying to improve port operation services, one of the efforts that has been made is building port facilities. There is an increase in loading and unloading activities of superior commodities, it is necessary to increase the quality. Efforts to maintain service quality of a company must analyze and serve data and information accordingly from data and measurements, in this case, product suitability and customer satisfaction levels. The purpose of this research is to measure the service quality of PT Delta Arta Bahari Nusantara uses 5 service quality dimensions, the measurement results (gap) between customer perceptions and expectations are evaluated by the Quality Function Deployment (QFD) method. Furthermore, based on the policy (gap) and QFD, strategies are formulated that must be carried out. The results of the analysis showed that all dimensions resulted in a satisfaction level of "less satisfied" (Gap value between -1.5 to -2.25) which means that in all dimensions of satisfaction, customer service ratings provided by PT Delta Arta Bahari Nusantara is not satisfied with meeting expectations. There are 5 indicators that require immediate improvement. Indicators that require the main priority for improvement are the condition and capacity of the dumping yard as well as the facilities and infrastructure, the layout of the stacking field facilities. Recommendations that can be given by the management are evaluating the maximum capacity with the number of storage for goods to determine the addition of the storage area, making improvements to the layout of the facilities and completing if there are lack of public facilities